2020
DOI: 10.1111/jcmm.15514
|View full text |Cite
|
Sign up to set email alerts
|

Calycosin inhibited autophagy and oxidative stress in chronic kidney disease skeletal muscle atrophy by regulating AMPK/SKP2/CARM1 signalling pathway

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 59 publications
3
26
0
Order By: Relevance
“…Notably, GCs induction of muscle atrophy-associated protein breakdown appears to involve effects on transcription factor production, specifically of forkhead box (Fox) O1, FoxO3a ( 12 ) and GSK3β ( 13 ), that trigger ubiquitin proteasome system-dependent proteolysis of muscle proteins and subsequent autophagy ( 14 ). Meanwhile, studies of muscle atrophy induced by denervation have identified increased mitochondrial fission and resulting fragmentation as key signals responsible for triggering the AMP-activated kinase-forkhead box O3 (AMPK-FoxO3) signaling pathway ( 15 , 16 ). Mitochondria are organelles that provide energy to cells.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, GCs induction of muscle atrophy-associated protein breakdown appears to involve effects on transcription factor production, specifically of forkhead box (Fox) O1, FoxO3a ( 12 ) and GSK3β ( 13 ), that trigger ubiquitin proteasome system-dependent proteolysis of muscle proteins and subsequent autophagy ( 14 ). Meanwhile, studies of muscle atrophy induced by denervation have identified increased mitochondrial fission and resulting fragmentation as key signals responsible for triggering the AMP-activated kinase-forkhead box O3 (AMPK-FoxO3) signaling pathway ( 15 , 16 ). Mitochondria are organelles that provide energy to cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although low muscle mass, low muscle strength and low physical performance are closely related, there is not yet an agreement on which operational criteria to apply when diagnosing muscle atrophy in CKD patients ( Sabatino et al, 2021 ). Muscle mass and physical performance were determined as direct indicators of muscle atrophy in CKD model rats based on our previous studies ( Wang et al, 2019 ; Hu et al, 2020 ; Liu et al, 2021 ). The PF-treated group was confirmed by an increase in body weight, muscle weight and muscle fiber CSA.…”
Section: Discussionmentioning
confidence: 99%
“…The nephrectomized group rats underwent a 5/6 nephrectomy surgical resection of the upper and lower thirds of the left kidney and were subjected to right nephrectomy after 1 week. The Sham group rats were treated as described previously ( Wang et al, 2019 ; Hu et al, 2020 ; Liu et al, 2021 ). Rats were observed postprocedure for 1–2 h, and their wound healing, movements, mental states and body weights were monitored weekly.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the molecular mechanisms linking pathogenetic factors in kidney brosis are complicated and incompletely understood 5,6 . It is most likely a combination of oxidative stress [7][8][9][10] , in ammation [11][12][13] , epithelial to mesenchymal transition, apoptosis 14 , and extracellular matrix deposition 15 . Thus, studies aimed at exploring attractive therapeutic targets and developing corresponding approaches for the treatment of CKD are urgently needed.…”
Section: Introductionmentioning
confidence: 99%